How Did the Lack of Russian Tourists Affect Tourism in South Karelia Region - Bochelenkova, Anastasiia (2023)
The purpose of this thesis is to examine the impact of the decrease in Russian tourists in South Karelia, Finland, which is attributed to Russia's invasion of Ukraine. Russian tourists have historically been the primary international group visiting the region. However, due to conflict, the tourist flow from Russia has changed significantly. This study was initiated to evaluate how geopolitical crises can affect cross-border tourism regions. This research focuses on how destination development organisations and tourism companies adapted to the changing market. The results are presented through the ADKAR model, one of the change management frameworks. This study utilises a qualitative method, incorporating literature reviews and semi-structured interviews. The literature review establishes a theoretical framework and destination overview. Simultaneously, interviews with local experts in the tourism and marketing industry provide valuable insights into the specific changes and effects resulting from the decrease in Russian travellers. Furthermore, the research shows that the consequences of the Russian-Ukraine war affected the tourism industry, leading to changes in tourist flow, decreased profits, shutdowns and tactics. The study showcases the strategies and new directions that regional DMOs employed, such as diversifying the tourist demographic and implementing alternative marketing activities. The thesis concludes by demonstrating the interdependence between regional tourism and global crises, shedding light on South Karelia's response to tourism's evolving landscape. Although the region still faces uncertainty, its proactive measures have already yielded positive outcomes through new strategies. Given the ongoing nature of the conflict, further research is necessary. The author suggests developing customised tourism experiences and offering various tourism products in the area. Further study is needed to fully understand the consequences of the conflict on tourism, examining the overall effects of war from ...